1984
DOI: 10.1007/bf02913943
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of cooperativity in vertebrate muscle thin filaments

Abstract: Extraction of as little as one troponin C per regulatory strand on a thin filament reduces the slope of the pCa/tension relation thus the regulatory units along a thin filament of rabbit psoas fibers are linked cooperatively so that a thin filament activates as a unit. This explains why the pCa/tension relation in skinned fibers has a slope much higher than can be expected by binding of Ca 2 § to one regulatory unit (BRANDT et al. 1980;BRANDT et al. 1982). These results also show that troponin C is the only my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…A summary of the data from all 13 myocyte preparations studied is shown in Fig. 6 B. The right shift seen in the tension-pCa relation after partial extraction of TnC is similar to that seen previously in skeletal muscle (Brandt et al, 1984;Moss et al, 1985). With readdition of bovine cardiac TnC, Ca 2+ sensitivity returned to control levels.…”
Section: Effect Of Tnc Extraction On the Tension-pca Relationship In supporting
confidence: 79%
“…A summary of the data from all 13 myocyte preparations studied is shown in Fig. 6 B. The right shift seen in the tension-pCa relation after partial extraction of TnC is similar to that seen previously in skeletal muscle (Brandt et al, 1984;Moss et al, 1985). With readdition of bovine cardiac TnC, Ca 2+ sensitivity returned to control levels.…”
Section: Effect Of Tnc Extraction On the Tension-pca Relationship In supporting
confidence: 79%
“…7). In addition, the threshold for tension production in ALD fibres (Brandt et al 1984;Moss, Giulian & Greaser, 1985 other than the stoichiometric ratio of TnC to other contractile proteins at this age.…”
Section: Neonatal Muscle Fibresmentioning
confidence: 94%
“…The tension generated by the neonatal ALD fibres is significantly less (P < 0-005) than that generated by the neonatal PM and PLD fibres and by the adult ALD fibres. Previous studies have demonstrated that the tension-pCa relationship for muscle fibres deficient in TnC is shifted to lower pCas relative to the curve for fibres with the normal complement of TnC and that TnC-deficient fibres also generate less than normal tension during maximal calcium activation (Brandt et al 1984;Moss, Giulian & Greaser, 1985). It was therefore necessary to test whether the shifts in the tension-pCa curve between neonatal and adult PM and PLD fibres were related to the relatively low PO/CSA of neonatal fibres compared to adult fibres, under the assumption that the low tension reflected a deficiency in TnC.…”
Section: Neonatal Muscle Fibresmentioning
confidence: 98%
See 1 more Smart Citation
“…Endogenous TnC from barnacle myofibrillar bundles was removed by incubation with a low ionic strength 2 mM Na 2 EDTA solution, a widely used extraction technique previously shown to selectively remove TnC from both vertebrate striated muscle fibres [7,8,23,29,44] and barnacle myofibrillar bundles [2,3,4,5,6,14,36]. In vertebrate striated muscle EDTA is thought to act by removing the Mg 2+ ions from the Ca 2+ /Mg 2+ sites (III and IV), thereby causing the dissociation of TnC from the thin filament TnI.…”
Section: Discussionmentioning
confidence: 99%